2007
DOI: 10.1016/j.jecp.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Auditory word identification in dyslexic and normally achieving readers

Abstract: The integrity of phonological representation/processing in dyslexic children was explored with a gating task in which children listened to successively longer segments (gates) of a word. At each gate, the task was to decide what the entire word was. Responses were scored for overall accuracy as well as the children's sensitivity to coarticulation from the final consonant. As a group, dyslexic children were less able than normally achieving readers to detect coarticulation present in the vowel portion of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…Note that only the SLI-D group, not the SLI-only group, performed significantly worse than the normal group in the speech gating and the lexical judgment task-both are putative measures of phonological representation. These findings lend support to earlier works that report inadequate phonological representations in English-speaking children with dyslexia (e.g., Bruno et al, 2007;Elbro et al, 1998;Elbro & Jensen, 2005;Swan & Goswami, 1997a, 1997b and suggest that Cantonese-Chinese-speaking children with dyslexia can be characterized by poorly segmented or poorly specified phonological representations, which might contribute to their difficulties in phonological awareness and phonological memory. Future research, however, is needed to confirm this suggestion with a group of children with a singular diagnosis of dyslexia and to rule out the possibility that children with SLI-only's phonological representations are also poorly segmented or underspecified with a larger sample of children.…”
Section: Discussionsupporting
confidence: 89%
“…Note that only the SLI-D group, not the SLI-only group, performed significantly worse than the normal group in the speech gating and the lexical judgment task-both are putative measures of phonological representation. These findings lend support to earlier works that report inadequate phonological representations in English-speaking children with dyslexia (e.g., Bruno et al, 2007;Elbro et al, 1998;Elbro & Jensen, 2005;Swan & Goswami, 1997a, 1997b and suggest that Cantonese-Chinese-speaking children with dyslexia can be characterized by poorly segmented or poorly specified phonological representations, which might contribute to their difficulties in phonological awareness and phonological memory. Future research, however, is needed to confirm this suggestion with a group of children with a singular diagnosis of dyslexia and to rule out the possibility that children with SLI-only's phonological representations are also poorly segmented or underspecified with a larger sample of children.…”
Section: Discussionsupporting
confidence: 89%
“…In other words, the awareness of phonemes appears to result from reading experience. Consequently, phonemic deficits observed in developmental dyslexics or poor readers are likely to be a consequence of their reading difficulties rather than a cause (Metsala, 1997;Ziegler and Goswami, 2005;Bruno et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Both speech perception accuracy and categorical organization have distinguished children with and without dyslexia in previous studies in Indo‐European languages (e.g., Bruno et al, 2007; Chiappe, Chiappe, & Siegel, 2001; Maassen, Groenen, Crul, Assman‐Hulsmans, & Gabreëls, 2001; Serniclaes, Sprenger‐Charolles, Carré, & Demonet, 2001). Other studies have demonstrated that event‐related potentials (ERPs) to speech sounds differ between children with dyslexia or at familial risk for dyslexia and controls, and that certain brain responses to speech sounds predict reading failure longitudinally (Leppänen et al, 2002; Lyytinen et al, 2005).…”
mentioning
confidence: 85%